Ответы и объяснения

2013-05-02T13:10:58+00:00

a) n/mn-n^2 = n/n(m-n) = 1/m-n = 1/3/4 = 1*4/3 = 4/3

б) m/mn-m^2 = m/m(n-m) = 1/n-m = -1/m-n = -1/3/4 = -4/3

в)n^2 - 2mn + m^2/ 3m-3n = (n-m)^2/3(m-n) = (m-n)^2/3(m-n) = (m-n)/3 = 3/4:3 = 1/4

Лучший Ответ!
2013-05-02T13:30:37+00:00

a)\frac{n}{mn-n^2}=\frac{n}{n(m-n)}=\frac{1}{m-n}=\frac{1}{\frac{3}{4}}=\frac{4}{3}

b)\frac{m}{mn-m^2}=\frac{m}{m(n-m)}=\frac{1}{n-m}=\frac{1}{-(m-n)}=\frac{1}{-(\frac{3}{4})}=-\frac{4}{3}

в)\frac{n^2-2mn+m^2}{3m-3n}=\frac{(n-m)^2}{3(m-n)}=\frac{(n-m)^2}{-3(n-m)}=\frac{n-m}{-3}=\frac{-(m-n)}{-3}=\frac{\frac{3}{4}}{3}=\frac{1}{4} 

 

Формула которую я использовал в в):

a^2-2ab+b^2=(a-b)^2